Evaluation of soil pollution caused by waste accumulation from an abandoned gold mine 50 years ago in La Planta, San Juan, Argentina - Heredia, Belen (2021)
Metal accumulation is the main soil pollution caused by abandoned gold mines.Metal(loid)s are not biodegradable and have high persistence in the environment. Theobjective of this study was to evaluate the degree of contamination generated by miningwaste in La Planta, San Juan, Argentina. Ten soil samples were randomly taken at twosampling sites: contaminated (S1) and reference sites (S2). A physicochemicalcharacterization was carried out. Total, mobilizable and soluble concentration of Cu,Cd, Zn, and As was determined. The Geoaccumulation Index (Igeo), ContaminationFactor (CF) and Contamination Degree (Cdeg) were calculated to know the pollutiongenerated by mining waste. Total concentration of metal(loid)s was contrasted withguideline values ​​for residential and agricultural use (Argentine Law no. 24,051). Anacid pH (=3) was recorded for S1 and slightly alkaline pH (=8) was recorded for S2. ECwas 8 times higher in S1, reaching a maximum value of 41.2 mS cm -1 . Essentialnutrients were less concentrated in S1. Total concentration of Cu, Cd, Zn, and As wasstatistically higher in S1 (p<0.001). The mobilizable and soluble fractions were 7 to38% of the total metal(loid) concentration in S1. While in S2, the mobilizable fractionwas 12 to 38% of the total concentration, and the soluble fraction was not detected. Theconcentrations of metal(loid)s were below the reference levels for both agricultural andresidential use in S2, while they were between 1 and 300 times above the referencelevels in S1. The highest concentrations were obtained for Zn (7123 mg kg -1 ) and As(6516 mg kg -1 ) in S1. A positive correlation was obtained between EC and the threefractions of the metal(loid)s in S1 (R>0.7; p<0.001). The pH correlated negatively withthe total and soluble fraction of As, and the mobilizable fraction of Zn (R>-0.7;p<0.001). Igeo reached values ​​higher than 5 for As, Cd and Zn in S1, categorized asvery strong contamination and Cu corresponds to the category uncontaminated tomoderately contaminated. Using CF values, S1 was classified as very highcontaminated site for all four metal(loid)s. Values of Cdeg showed the highest categoryof contamination. Results indicate that soil is contaminated with at least Cu, Cd, Zn andAs in La Planta, showing the need to carry out a remediation plan. We conclude thatsoil pH should be regulated in order to reduce the bioavailability of metal(loid)s andpromote plant growth.